Suicide, demographic, socio-structural, infrastructure and crime statistics of the German Democratic Republic, 1952-1990 - Driesch, Ellen von den (WZB, 2020)
The data set contains 503 variables and 624 observations on suicides and suicide rates as well as on demographic, socio-structural, infrastructure and crime statistics on the canton and national level for the years 1952 to 1990. The information was recorded and processed by GDR’s Central Bureau of Statistics on a yearly basis. The statistical yearbooks of the GDR and various files of the Federal Archive were used as the sources of this data. The demographic statistics include the population distribution by gender and age-groups, the incidence of deaths, homicides, births, stillbirths, as well as infant mortality and domestic migration rates by year and administrative district. The socio-structural information includes marriage and divorce rates, population distribution by education, employment and religious denomination, as well as the number of members and candidates of the Socialist Unity Party of Germany by year and district. The infrastructure data contains information on population density, residential housing construction and retail sales by year and administrative canton. The annual numbers of offenders of criminally liable age and convicted persons in the districts that come from the GDR crime statistics were included in the data set from the GDR crime statistics. Missing values indicate that no information could be found for the given year or region. However, the missing information on the distribution by gender and age-groups, as well as suicide rates by age-group can be estimated using the attached do-files. A detailed description of how the missing values have been determined can be found in the document “Imputation und Standardisierung.pdf”. The do-files and the description are available in a zip file below.